FORMULASI SEDIAAN HAIR TONIC EKSTRAK BIJI KETUMBAR (CORRIANDRUM SATIVUM L) SEBAGAI PENUMBUH RAMBUT PADA TIKUS PUTIH (Rattus Norvegicus) - Irza Haicha Pratama; Dewi Asri Sirait; Viona Masniari; Reshot Maria; Andre Budi (Universitas Prima Indonesia, 2023)
Background: Coriander seeds (Coriandrum sativum L) contain linalool in them, causing antibacterial properties (Coriandrum sativum L.) (Hamudeng, 2017). Coriandrum sativum L, also known as a spice, is commonly used in Indonesia. It has various bioactive ingredients, including flavonoids, terpenoids, and polyphenols, which have medicinal effects. In addition, it is known that Coriandrum sativum has various pharmacological properties, including antioxidant, antidiabetic, and anti-dyslipidemia. (Irza, 2022). Purpose: To find out how to make hair tonic using coriander extract (corriandrum sativum L). To determine the characteristics of the physical properties and the pH of the tonic hair preparation of coriander seed extract. Methods: Experimental research will be used. Experiments were conducted to determine the best proportion of active ingredients from a mixture of coriander extracts to make hair tonic preparations. This experiment aims to produce tonic hair products that meet SNI. Materials: In this study, 15 white rats (Rattus norvegicus) were used as materials. Tools: PH meter. Results: Our hair tonic research showed that all preparations were stable for 28 days and stored at room temperature, and did not change color, smell, or texture. The results of the homogeneity test showed that there were no small grains during observation. Compared to formulas I and II, formula III produces the most stable preparation by producing less precipitate. Therefore, this is the best formula because F1 and F2 precipitate on the 21st day. However, the precipitate that can be redispersed is the precipitate resulting from the three formulas. Conclusion: Concentrations of coriander seeds 2.5%, 5.0%, and 7.5%, respectively, have a cloudy brown color, black-brown, and a distinctive aroma of coriander seeds which are weak, medium, and strong. They also meet the quality requirements of SNI 16-4955-1998 hair tonic, which is homogeneous and does not contain foreign particles. According to the pH test of Durante Hair Tonic, the average pH value is around 6.5, with a standard deviation of 0.10284. As a result of the pH values â€‹â€‹observed in this study, it can be concluded that this hair care product with coriander seed extract meets the standards. Â